Pembinaan Siswa untuk Meningkatkan Kemahiran Membaca Al-Qur'an dengan Metode Tilawati di SD IT Al-Qonita - Ulfah Islamiah; Sulistyowati Sulistyowati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The challenge in learning the Al-Quran at SD IT Al-Qonita is the difference in the background of students' initial abilities in reading the Al-Quran which causes a gap in abilities between students. This affects the effectiveness of learning, where some students need more time and assistance to achieve basic competency in reading the Al-Qur'an. This research aims to evaluate the implementation of the Tilawati method at SD IT Al-Qonita, identify the obstacles faced, and provide strategic recommendations to increase learning effectiveness. This research uses the Participatory Action Research (PAR) method. The results of this research show that after carrying out Al-Quran reading guidance for students at Al-Qonita IT Elementary School, Palangkaraya City, they succeeded in increasing the students' ability to read the Al-Quran well and correctly more evenly. This program not only teaches how to read the Al-Quran, but also fosters students' interest and motivation to continue learning and practicing reading the Al-Qur'an in everyday life both at school and at home. The application of the Tilawati method in Al-Qur'an reading training at SD IT Al-Qonita has proven effective in improving the quality of learning.